Impact of COVID-19 on Opioid Prescribing, Consumption, Pain, and Outcomes after Surgery - Dorna Kheirabadi, MD; Vidhya Gunaseelan, MBA, MS, MHA; Yenling Lai, MSPH, MS; Chad M. Brummett, MD; Jennifer F. Waljee, MD, MPH, MS; Michael J. Englesbe, MD; Mark C. Bicket, MD, PhD (Annals of Surgery Open, 2025)
Objective:. The aim is to compare opioid prescription, consumption, and patient-reported and clinical outcomes after surgical discharge pre- versus post-COVID-19 pandemic. Background:. Numerous studies have demonstrated negative health outcomes after pandemic onset. However, the impact on postoperative opioid use, pain, and relevant outcomes is unclear. Methods:. Using interrupted time series analysis, we examined opioid-naive adults undergoing a variety of surgical procedures across 69 hospitals in a statewide quality collaborative, adjusting for demographic and clinical factors. We compared postsurgical outcomes in the prepandemic period (June 1, 2018–February 29, 2020) and the postpandemic period (June 1, 2020–December 31, 2021). Primary outcomes included 30-day opioid prescriptions and patient-reported consumption; secondary outcomes included patient-reported pain, quality of life, satisfaction, and surgical regret; and the composite outcome included 30-day complications, readmissions, and emergency department visits. Results:. The primary analysis included 18,031 patients in the prepandemic group and 19,973 in the postpandemic group. Adjusted analyses showed no significant impact of the pandemic on opioid prescribing (level change in any prescription: −0.012 [95% confidence interval (CI): −0.073 to 0.048]; number of pills prescribed: 0.863 [95% CI: −0.277 to 2.003]) or opioid consumption (level change in amount consumed: 0.614 [95% CI: −11.748 to 12.977]). No differences appeared in patient-reported outcomes or composite outcomes of 30-day complications, readmissions, and emergency room visits (P for all level change >0.05). Conclusions:. The absence of significant changes in opioid prescribing or consumption, clinical outcomes, and patient-reported outcomes suggest that certain quality improvement outcomes may have been resilient to disruptions caused by the COVID-19 pandemic.